Analisis Hukum Yayasan Pendidikan Tinggi Sebagai Wajib Pajak Penghasilan - A. Zulkarnain (LPPM Universitas Ekasakti Padang, 2023)
This research focuses on the Legal Analysis of Higher Education Foundations as Income Tax Subjects. The research method employed is normative juridical with a conceptual, theoretical, legislative, and case approach. The data used consists of secondary data in the form of primary and secondary legal materials. The research results indicate that Higher Education Foundations now have legal certainty as Taxable Entity subjects, with obligations to Withhold, Deposit, and Report (3M) Article 21 Income Tax under Law No. 36/2008 for activities falling under Article 21 Income Tax, Article 4 paragraph (1), such as salaries/wages of teachers, allowances, honorariums paid to employees or participants, and other parties. Income received or obtained from business activities, work, or services, deduction of registration fees for new students, student tuition fees, etc.; Article 4 paragraph (2) gains from the utilization of foundation assets, etc.; Article 23 Income Tax on architectural services for the construction of foundation education buildings. These amounts are then deposited at the post office or bank designated by the Minister of Finance. Furthermore, Taxpayers, Tax Withholders, and Tax Reporters, if found in violation of tax regulations, will face sanctions, including Administrative Sanctions under Article 7 Paragraph 1 of Law No. 6 of 1983 concerning General Provisions and Taxation Procedures (Tax Law) for failure to report Tax Returns, Article 9 Paragraph 1 and 2a Tax Law for late payment or deposit of taxes to the state treasury; Article 13 Paragraph 1 Tax Law for underpayment of taxes for 5 consecutive years. Criminal Sanctions will be applied according to Article 39 Paragraph (1) Tax Law for negligence of tax withholders in providing withholding or collection proof.